Science for Development: Mobilizing Global Partnerships - Deane, Christine; Ejeta, Gebisa; Rabbinge, Rudy; Sayer, Jeff (Wiley, 2010)
Investment in agricultural research has consistently delivered high rates of return in terms of increasing productivity, improving nutrition, and reducing poverty.1 This is the mandated aim of the Consultative Group on International Agricultural Research (CGIAR). A route therefore exists through agricultural research to boost food resources, improve livelihoods, enhance quality of life, and underpin the stability of societies in the developing world. Supporting quality and relevant agricultural research must be a priority for all development cooperation as well as stability and security agendas. The challenges to food security in developing countries are great, but so are the opportunities for developing solutions. The number and scope of possible avenues for research are extensive. They range from scientific problems, where the focus is on bio-molecular and biophysical research, to regional- and global-level challenges, where meshing technological innovations with social, institutional, and economic research dominates. Demands exceed the funds available. The importance of selecting strategic research directions that will have the greatest impact is clear. The CGIAR invests in research that increases the productivity of agricultural and natural resource systems in the developing world. Tactical partnerships are vital to conduct and to inform the research. Entering into partnership arrangements that present a genuine value-added proposition has been central to the CGIAR's successes in its impact-oriented research. Partnerships that connect development-focused agricultural research with the extensive research capacities of the developed and emerging economies can increase the returns on donor countries' broader investment in research. The CGIAR has been leveraging donor funds through its strategic investment choices for almost half a century. As a consortium of 15 agricultural research Centers, largely situated in developing countries, and supporting several major collaborative research programs, it is uniquely positioned as a partner in research. Planning and conducting global public goods research requires highly effective partnerships between the appropriate providers of ideas, new knowledge, technology, social science understanding, and policy processes. Ensuring that pathways to disseminate useful advances are available will equally require cooperation between the CGIAR and other parts of the research community that help to translate and adapt research results to ensure on-the-ground impact. Each workshop addressed the following questions: What is the frontier science in this area? Where is the potential for impact on sustainable food security and international development goals? What are the research needs, and what other changes are needed, if this potential is to be realized? Which applications are the most feasible for achieving impact through take-up into national agricultural research systems within a short time-frame (3–5 years), and which have longer time horizons? The current issue of Crop Science offers a selection of the papers presented and debated during these workshops. Participants agreed that the major challenge ahead is to double primary food production in a sustainable way within the next three decades, and that this increase must be achieved largely through improvements in agricultural productivity, as limits on the availability of land and the scarcity of other inputs will persist. In addressing this challenge, the Forum concluded that there is a pressing need to introduce new paradigms for agricultural productivity and agricultural research. One example of this is the concept of resilience. The impacts of climate change, market volatility, and other global, regional, and local shocks (e.g. induced by political volatility or environmental changes) have raised the suggestion that in striving to enhance food security, resilience should be considered alongside productivity. There had been some perception that the concepts of 'resilience' and 'productivity' are incompatible, but although there may be necessary trade-offs between the two, these concepts should be considered to be complementary. Attaining sustainable increases in production requires that the processes involved do not have secondary effects that feedback negatively on the functioning of the resource base, and therefore on flows of other valued goods and services. Adopting a resilience approach aims to ensure that gains in productivity lead to sustained increases in human well-being. In this current issue of Crop Science, Walker et al. (2010) explore the concept of resilience, and examine when and how enhanced resilience might become an objective of research. Broadening the foundation of the global food supply is similarly a crucial factor in striving to improve food security and enhance nutrition. Currently we rely on just 15 plant species and eight animal species for more than 90% of all human food (Convention on Biological Diversity, 2008). The intensive research focus on wheat, rice, and maize often discounts many valuable opportunities in underutilized crops. The Forum explored untapped opportunities that exist here, such as developing better cultivation methods for underutilized crops, and the use of biofortification to boost micronutrient content. Bouis and Welch (2010), Hubert et al. (2010), and Keatinge et al. (2010) discuss the challenges and opportunities in this field. Developments in ICTs are transforming the ways in which knowledge, information, and data are generated, used, and shared in many different fields. These developments are widely recognized to have valuable applications in efforts to improve agricultural productivity, promote sustainable practices, and contribute to the efficient operation of markets. Although the potential is great, harnessing this potential for the benefit of the developing world requires greater strategic investment and adaptation to the specific needs of developing countries. Ballantyne et al. (2010) explore these issues further. Powerful new molecular tools developed in recent decades offer ever greater opportunities to develop improved crops. The process of identifying gene function is particularly intractable in wheat and barley, due to the size and complexity of their genomes, and inherent difficulties in achieving genetic transformation in these plants. Cakir et al. (2010) present a system of virus-induced gene silencing as a useful new tool that overcomes many of these obstacles and promises to greatly facilitate the assessment of gene function. It was noted during the meeting that achieving increases in yields requires a combination of improved genotypes, optimal agronomic management, and the timely availability of appropriate inputs. Research aimed at improving the genetic makeup of crops, therefore, should advance hand-in-hand with better knowledge of crop physiology and agronomy, and a greater capacity to understand the complex phenotypic responses of crops in the field. Discussions on this topic concluded that research programs on genetic improvement should take this into considerations in their design, and avoid viewing molecular genetic improvement in disciplinary isolation. Fischer and Edmeades (2010) and Phillips (2010) discuss this in more depth. Climate change featured in discussions throughout the Forum, and Baethgen (2010) emphasizes the need to consider risk management in policymaking for adaptation to climate variability. The need to increase efficiency in the use of resources in agricultural production was also raised in discussion throughout the Forum. Production ecological principles are based on the notion that a production factor is most efficiently used when other required factors are at their optimum. Inputs should therefore be balanced to crops' needs in time and space, considering location-specific ecological conditions, in order to yield the highest returns on those inputs. Spreading these principles is urgently needed, as they can help to improve agriculture in developing countries. The concept of eco-efficiency is multi-dimensional, encompassing both ecological and economic dimensions of sustainable agriculture. Although social and institutional aspects of sustainability are often not explicitly captured in eco-efficiency measures, they present significant obstacles as well as opportunities when trying to transition to more eco-efficient agriculture, and as such, they should be taken into account. Risk remains a critical factor influencing the uptake of more eco-efficient measures. In striving to achieve greater eco-efficiencies and increase sustainable food production in the developing world, those risks most relevant in the context of developing country agriculture must be taken into consideration. Keating et al. (2010), Lal (2010), and Park et al. (2010) discuss different aspects of these issues. The advent of bio-based products (e.g. flavors, biomolecules, bioplastics etc.) and the development of a bio-based economy have often been hailed as a means of expanding sustainable production, but there are critical resource concerns, which are particularly acute in the developing world (e.g. the conflicting demands for resources used for food and for biofuel production). As bio-based production is being increasingly promoted and adopted, rational advice to guide the development of initiatives and incentives is essential. Debate on this topic at the Forum explored these concerns, and questioned whether research should focus on improving the efficiencies of first-generation biofuels, for example, or whether greater effort should be directed towards first assessing the social, economic, and environmental impacts of their production in developing countries. An alternative focus would be to direct research to a far greater extent towards initiatives that are more likely to yield bio-based products and production systems that compliment rather than compete with food production. Langeveld et al. (2010) and Hatti-Kaul (2010) discuss the challenges, the opportunities, and the complexities of these issues. Mollinga (2010) emphasized that more attention should be focused on the boundaries between different research disciplines, and those between research and policy, when addressing sustainable agricultural production and natural resource management in the developing world. Indeed, a consistent theme that arose during the meeting was the need for more cross-disciplinary cooperation in research programs that seek to address these kinds of complex challenges. Incentive mechanisms that are well-crafted and adapted to facilitate these kinds of collaborations were considered essential. The need for people with 'T-shaped' skill sets (i.e. being specialists in one discipline and knowledgeable across complimentary disciplines at the same time) was also highlighted. Another common theme that emerged in discussion was the importance of considering without prejudice all possible research tools and technologies that can potentially contribute to solutions. As a cooperative effort of the CGIAR centers, the Science Council, and advanced research institutes, the CGIAR Science Forum 2009 represented a positive step towards broadening the engagement of the international scientific and development communities in research that holds significant potential to contribute to food security. The Forum identified areas of rapid scientific innovation where opportunities exist, and explored new modalities for research collaboration and partnership. It debated which areas of research hold the greatest promise for international development, where the most pressing research needs are, and what kinds of collaborative work and partnerships should be supported to realize this potential. The meeting also provided a forum in which to engage the broader research community in the science-for-development mission. The findings and concluding directions arising from the Forum, presented in part in the papers in this current issue of Crop Science, can serve to guide the current debate on refining and refocusing the CGIAR's research agenda. They also offer elements for consideration in broader discussions on designing science-for-development agendas in other contexts. Some of the key conclusions have immediate relevance to the CGIAR, and could be adopted as part of the new research agenda (CGIAR Mega Programs). As the CGIAR transitions to a new research agenda, there is, for example, an opportunity to factor in the concept of resilience across the Mega Programs. Likewise, crop improvement programs relying on advances in molecular genetics should be more closely developed with programs aimed at developing a better understanding of relevant crop physiology and agronomy. Further, by including social as well as economic and environmental criteria in the development of eco-efficiency tools and technologies, research portfolios would take on a more holistic approach to the issues constraining development. Ultimately, the CGIAR Science Forum 2009 called for a new paradigm in agricultural research for development, where partners in research, donors, and communities in the developing world together realize better strategies to reach the goal of doubling food production within the next 30 years.